Significance of technological progress and capital formation to expand foreign direct investment in Bangladesh: Does money circulation matter? - Tasin Safwath Chowdhury; Md. Hasanur Rahman; Shapan Chandra Majumder; Miguel Angel Esquivias Padilla (Cogent Economics & Finance, 2023)
The key objective of this study is to investigate how capital formation and technological advancement affect foreign direct investment (FDI) generation in Bangladesh and whether money circulation has a positive or negative impact on FDI. This study has used time series data from 1972-2021, and the result of the unit root test indicates an autoregressive distributed lag (ARDL) model because of stationarity at levels I(0) and I(1). The cointegration test confirms the cointegration among the variables: in the short run and long run, capital formation and technological advancement have a positive impact on FDI; on the other hand, money circulation discourages FDI because of its negative coefficient. The speed of adjustment (CointEq(−1)) is 0.28%, which indicates the estimation moves toward an equilibrium condition from a disequilibrium condition. Causality shows there is bidirectional causality between FDI and money circulation, unidirectional causality between technology and FDI, bidirectional causality between money circulation and capital formation, and unidirectional causality between technology and capital formation. This finding suggests that capital formation should be a great consideration, and technology is also required to expand FDI volume. Further study would include considering other macroeconomic variables such as labor, human resources, and energy issues.
Keywords: 330; capital formation; Foreign Direct Investment; money circulation; sustainability; technological progress